2023
DOI: 10.52711/0975-4385.2023.00021
|View full text |Cite
|
Sign up to set email alerts
|

A Review on: Phytoconstituents, Traditional and Medicinal uses of Taraxacum offinale (Dandelion)

Abstract: Since 5000 BC, medicinal plants have been used in India as part of the Ayurvedic medical system. Medical professionals frequently use herbal remedies. Taraxacum officinale, commonly called dandelion, is a perennial plant belonging to the family Asteraceae. It is also known as wet-a-bed, lion’s tooth, priest’s crown, blowball, milk gowan, wild endive, white endive, puffball, and Irish daisy. Long and upright flowering stalks with a single terminal inflorescence are present. It has numerous medicinal properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Tannins are also responsible for decreased growth rate, food absorption, energy metabolism and protein digestibility. Eggum and Christensen (1975), Kumar et al (2012), discovered that the addition of tannic acid to the diet of rats decreased the digestibility of protein and amino acids and the use of metabolic proteins. Mehansho et al (1987) demonstrated that tannins can bind to epithelial cells and cause subsequent precipitation of proteins that penetrate the cells surface, causing damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins are also responsible for decreased growth rate, food absorption, energy metabolism and protein digestibility. Eggum and Christensen (1975), Kumar et al (2012), discovered that the addition of tannic acid to the diet of rats decreased the digestibility of protein and amino acids and the use of metabolic proteins. Mehansho et al (1987) demonstrated that tannins can bind to epithelial cells and cause subsequent precipitation of proteins that penetrate the cells surface, causing damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have made large contributions in the enhancement of human health and wellbeing via its leaves, fruits and roots, which have remained important components of healthy diets. Fruits and other edible plant parts have contributed greatly due to their high content of vitamins, minerals, fiber and beneficial non-nutrient substances often referred to as nutraceuticals (Kumar et al, 2012) [14] . The medicinal benefits of fruits are based on their ability to aid in the body's retention of calcium, nitrogen, iron and phosphorus, all of which work to build healthy organs and regenerated tissues.…”
Section: Introductionmentioning
confidence: 99%
“…prevent raising blood pressure and muscle cramps and resist venereal diseases(Ekesa et al, 2015). Furthermore, banana does not contain even trace amounts of fat, cholesterol, or sodium which makes it a healthy food option even for restrictive diet plans (SampathKumar et al, 2012) Ferreira et al, (2013). stated that fruits and vegetable flour are rich in crude fiber, protein and minerals and have a high-water holding capacity and oil holding capacity.…”
mentioning
confidence: 99%